2000
DOI: 10.1097/00042752-200001000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Knee Pain: A Clinical Comparison of Rehabilitation Methods

Abstract: Findings suggest that the Muncie method results in improved clinical outcome at a lower cost than traditional home and physical therapy and possibly improved VMO/quadriceps muscle balance. Patients with anterior knee pain may benefit from applying the Muncie method in a home therapy program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 23 publications
0
31
0
1
Order By: Relevance
“…Several trials 8,15,20,52 have investigated the use of a combined treatment approach in the management of PFPS. Except for 1 trial, 15 each demonstrated a relatively short-term treatment effect in improving pain and function 20,52 or the rate of discharge from physical therapy based on patient satisfaction.…”
Section: Combined Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials 8,15,20,52 have investigated the use of a combined treatment approach in the management of PFPS. Except for 1 trial, 15 each demonstrated a relatively short-term treatment effect in improving pain and function 20,52 or the rate of discharge from physical therapy based on patient satisfaction.…”
Section: Combined Treatmentsmentioning
confidence: 99%
“…Except for 1 trial, 15 each demonstrated a relatively short-term treatment effect in improving pain and function 20,52 or the rate of discharge from physical therapy based on patient satisfaction. 8 Two of the 4 trials 8,20 also had quality scores that exceeded 70 points (Table 5).…”
Section: Combined Treatmentsmentioning
confidence: 99%
“…In the literature, researchers demonstrated that patients with PFPS can benefit from isometric quadriceps exercises and straight leg raise exercises (31,32). Roush et al investigated the effects of the modified straight leg raises exercises (called the 'Muncie method') for patients with PFPS (32).…”
Section: Open Kinetic Chain Exercisementioning
confidence: 99%
“…Roush et al investigated the effects of the modified straight leg raises exercises (called the 'Muncie method') for patients with PFPS (32). The authors evaluated pain, functional level and isokinetic strength of the quadriceps muscle at the beginning and end of the treatment (32). They noticed that patients who performed the quadriceps-strengthening home exercises programme and modified straight leg raises exercises reported significantly improvements regarding pain and functional level (32).…”
Section: Open Kinetic Chain Exercisementioning
confidence: 99%
See 1 more Smart Citation